Association of two clones allows for optimal detection of human FOXP3 - Presicce, Pietro (2010)
FOXP3 is a key transcription factor expressed by regulatory T cells (Treg cells). However, differences in staining and analysis protocols have led to conflicting results. Moreover, the transient upregulation of FOXP3 that follows activation in non-Treg cells renders the interpretation of FOXP3 data more difficult in humans than in mice. Human Peripheral Blood Mononuclear Cells (PBMCs), isolated CD25(−) or CD25(+)CD4(+) T cells were stained with three different anti-FOXP3 clones (PCH101, 206D and 259D) alone or in combination, and using different permeabilization methods. FOXP3 expression was evaluated following T cell activation by several pathways. Gating based on a population that did not express FOXP3 (such as CD3(−)CD4(−) T cells) allowed for the optimal characterization of Treg cells. The 206D clone detected a lower percentage of cells than PCH101 or 259D. In contrast, 259D stained a population of activated T cells that PCH101 did not. Staining with two clones together consistently increased the proportion of FOXP3(+) cells. However, it is likely that only the double positive cells are Treg cells, as they expressed the highest CD25 and lowest CD127 levels. Our results emphasize that the choice of staining protocol leads to very different results concerning the frequency of Treg cells in humans. A more consistent identification of these cells will improve the knowledge of their biology, particularly during disease processes.